Berbamine and thymoquinone exert protective effects against immune-mediated liver injury via NF-κB dependent pathway - Kathem, Sarmed H.; Abdulsahib, Waleed K.; Zalzala, Munaf H. (Frontiers in Veterinary Science, 2022)
Background: Immune-mediated hepatitis is a serious threat to human health, and there is currently no effective treatment available, so new, safe, and low-cost therapies are desperately needed. Berbamine (BE), a natural substance obtained primarily from Berberis vulgaris L, is a traditional herbal medicine with several bioactivities such as antimicrobial and anticancer activities. Thymoquinone (TQ), a phytochemical molecule derived from the black cumin seeds of the Nigella sativa plant, has attracted interest due to its antioxidant, anti-inflammatory, and anticancer properties. Aim: To study the protective effects of BE and TQ in Concanavalin A (ConA)- induced acute liver injury and the underlying mechanism of action. Methods: sixty mice of both sexes were used, and divided into 4 groups( each group with 6 mice) as follows: Group I: received distilled water (negative control group). Group II: received distilled with a single dose of 0.1 ml ConA (20 mg/kg) on day 4 by retro-orbital route (model group). Group III and IV: received BE (30 mg/Kg/day) and TQ (25 mg/Kg/day) respectively by oral gavage for 4 successive days, with a single dose of ConA (20mg/kg) on day 4, then all animals were sacrificed after 8 hours and prepared for liver and blood collection. Results: ConA administration increased the ALT, AST, TNF-α, INFγ, and NF-κB significantly (p ˂0.001) in the model group. Both BE and TQ can reduce these parameters significantly (p ˂0.001) in group3 and 4 respectively when compared to the model group. Conclusion: Both BE and TQ prominently attenuated ConA immune-mediated liver injury. These findings propose a novel insight into developing a new therapeutic agent for treating hepatitis and other autoimmune diseases.